Managing the spatial externalities of renewable energy deployment: Uniform vs. differentiated regulation - Charlotte Geiger; Paul Lehmann (Helmholtz-Zentrum für Umweltforschung (UFZ), 2021)
With the expansion of renewable energy sources (RES) in countries all over the world, policy design to address the negative impacts of RES plants on their local and regional environment gains in importance. We analyse whether policy design should be spatially-differentiated or uniform when negative RES environmental externalities are spatially heterogeneous and display interregional cumulative effects. In a theoretical model of the RES electricity generation sector, we compare the welfare differential between both regulatory designs and analyse how it is affected by cumulative environmental effects. While we confirm that the welfare costs of attaining a RES deployment target are lower under a spatially-differentiated than a spatiallyuniform regulation, we find that the welfare costs are contingent on the presence of cumulative environmental effects. This depends on the heterogeneity of region-specific generation cost parameters and social cost parameters of RES electricity generation. If heterogeneity is more (less) pronounced in regional generation cost parameters than in regional social cost parameters, positive (negative) cumulative effects decrease the welfare costs of a uniform instrument.
Keywords: D61; D62; H21; H23; Q48; Q58; 330; environmental regulation; renewable energy subsidies; regional environmental damages; interregional environmental damages; renewable energy deployment